The Effect of Work Environment, Work Discipline, and Motivation on Employee Performance: A Case Study of Sanctoo Suites & Villas, Gianyar Regency - Putri, Anak Agung Mira Shylla; Widyawati, Sapta Rini; Saraswati, Ni Putu Ayu Sintya (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to determine the influence of work environment, work discipline, and work motivation on employee performance at Sanctoo Suites & Villas Gianyar Regency. This study is associative in nature. The population in this study consisted of all 45 employees of Sanctoo Suites & Villas Gianyar Regency. The sampling technique used was Saturation Sampling Technique, where the entire population in this study was taken as a sample. The data analysis technique used was multiple linear regression analysis. The results showed that the work environment had a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work environment, the better the employee performance would be. Work discipline has a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work discipline, the better the employee performance will be. Work motivation has a positive and significant effect on employee performance at Sanctoo Suites & Villas in Gianyar Regency, meaning that the better the work motivation, the better the employee performance will be.